A Simple Mean-Field Diagnostic from Stokes V Spectra. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Gayley, K. G.; Owocki, S. P.
Abstract: It is shown that the diagnostics from an observed circularly polarized line in a rapidly rotating star are directly interpretable, not in terms of the observed Stokes V profiles, but in terms of its antiderivative with respect to wavelength (in velocity units if preferred). This also leads to a new mean-field diagnostic that is just as easily obtained as the standard "center of gravity" approach, and is less susceptible to cancellation if the line-of-sight field changes sign over the face of the star.